PENGARUH INSIDER OWNERSHIP, INSTITUTIONAL OWNERSHIP, DISPERSION OF OWNERSHIP, TINGKAT PERTUMBUHAN PERUSAHAAN, DAN RISIKO PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2003-2006 - Tri Rahmawati, Christina Heti (Widya Warta, 2011)
To know partially the effect of insider ownership, institutional ownership, dispersion of ownership, degree of firm growth, and firm risk on dividend policy in firms that listed at Indonesia Stock Exchange of 2003–2006 period is the main purpose of this research. The other purpose is to know simultaneously the effect of insider ownership, institutional ownership, dispersion of ownership, degree of firm growth and firm risk on dividend policy in firms that listed at Indonesia Stock Exchange of 2003-2006 period. The population of this research was all the firms that listed at Indonesia Stock Exchange of 2003-2006 period namely, 266 in number. The sample, 35 firms, was taken by the use of purposive sampling method. The technique of data collection used was documentation. The data were obtained from center of stock exchange data, Faculty of Economics and Business, Gadjah Mada University of Yogyakarta. The data analysis made use of multiple linear regression method. The results showed that partially insider ownership had a negative effect on and was not significant to dividend policy. Institutional ownership had a positive effect on but was not significant to dividend policy. Dispersion of ownership had a positive effect on but was not significant to dividend policy. Degree of firm growth had a negative effect on and was significant to dividend policy. Firm risk had a negative effect on but was significant to dividend policy. Simultaneously insider ownership, institutional ownership, dispersion of ownership, degree of firm growth, and firm risk had a positive effect on and were significant to dividend policy.